Annual versus biannual azithromycin mass drug administration for the elimination of infectious trachoma in Africa: protocol for a systematic review and meta-analysis using data from individual communities - Jeremy David Keenan; Solomon Aragie; Taye Zeru; Getu Degu (BMJ Open)
Introduction Trachoma is an infectious eye disease caused by Chlamydia trachomatis and the leading infectious cause of blindness worldwide. WHO recommends community-wide oral azithromycin treatment as part of its trachoma elimination strategy. WHO initially recommended mass drug administration (MDA) with azithromycin once per year for several years, followed by reassessment. However, some districts have failed to eliminate trachoma even after a decade of annual MDA with azithromycin. As a result, WHO has recently advocated for more frequent antibiotics in districts with persistent trachoma. Although no specific frequency of antibiotic distributions has been recommended, several randomised trials have compared annual with biannual mass azithromycin distributions. This review aims to synthesise the available data to assess the effectiveness of biannual azithromycin MDA relative to annual MDA.Methods and analysis PubMed, Embase, Web of Science, Scopus and Google Scholar will be searched for studies comparing annual and biannual mass azithromycin distributions for trachoma. Community-level data will be extracted using a standardised data extraction form. Authors will be asked to contribute community-level data not available in the manuscript. The main outcome will be C. trachomatis infection among 1–9-year-old children, expressed as a community-level prevalence. A secondary outcome will be the presence of trachomatous inflammation-follicular. The analysis will follow principles of a one-stage individual participant data meta-analysis using complete case mixed-effects regression models with a random effect for study to model community-level prevalence data. Statistical heterogeneity will be assessed with the I2 statistic.Ethics and dissemination The research will use community-aggregated data and is thus exempt from ethical approval. The results will be submitted for publication in a peer-reviewed journal.PROSPERO registration number CRD42024526120.